Action on health screening and education to disseminate and improve the health status of the elderly - Widiyanti, Septi; Fibrila, Firda; Herlina, Herlina; Ridwan, M; Lestari, Gangsar Indah; Puspitaningrum, Elisa Murti (Research and Social Study Institute, 2024)
Indonesia has an alarming trend where from year to year the prevalence of degenerative diseases continues to increase, especially in the elderly. This condition is further exacerbated by the number of elderly people in Indonesia reaching 10.48% in proportion to 1 elderly person supported by the productive age population. In addition, there are still many elderly people who are vulnerable due to a lack of preparation both financially and non-financially. The implementation of this health screening action aims to stimulate the growth of disease prevention behavior in old age through education and disease screening activities. The methods used are counseling and health checks. As a result of this activity, 24 elderly people voluntarily participated in health screening. The health condition of the elderly in neighborhood V of Margodadi Village, South Metro District was identified. As many as 95.8% of the elderly are in an unhealthy condition. At least they have 1 problematic health indicator including BMI status, blood pressure, temporary blood glucose value, and uric acid. With details: hypertension 75% (18 elderly), high uric acid levels, 41.6% (10 elderly), and there is 1 elderly who has a malnutrition status based on BMI. It is important to provide assistance, especially for the elderly who are malnourished, to pay attention to food consumption that meets balanced nutritional standards. If possible, provide additional food such as mung bean porridge or other types and do physical activity to increase the metabolism of the elderly body which can support to improve the quality of life.